EP-198 Is Primary surgical treatment of anal carcinoma safe and cost-effective in low resource settings?. (9th August 2022) - Weledji, Elroy
Abstract: Aims: The aim of the study is to debate if primary surgical treatment (abdominoperineal (AP) resection remains safe and effective in low resource settings especially when considering the cost, availability, protracted treatment and complications of radiotherapy+/- chemotherapy. Methods: An electronic literature search were performed to identify original published studies on anal carcinoma and management. Results: The oncological outcome of primary surgical treatment is equivalent to chemoradiotherapy. The arguments for surgery as primary treatment are (1) Surgery is the primary treatment modality for small perianal lesions that can be locally excised, (2) a 55% 5-yr survival after a potentially curable AP resection of early locally advanced cancer, (3) 50% relapse after complete remission using chemoradiation and many can be salvaged by AP resection. (4) Four situations may require surgery after primary chemoradiotherapy (a) residual tumour, (b) complications of treatment, (c) incontinence or fistula after tumour resolution, (d) subsequent tumour recurrence. (5) Only a generous biopsy will reveal if a residual ulcer contains residual disease for which a salvage AP resection may be the only option as further radiotherapy cannot be given. (6) Salvage AP resection carries a high morbidity. The main arguments against surgery as primary treatment are the increased tumour radiosensitivity in the undisturbed pelvis with well oxygenated tissues and less small bowel in the radiation field limiting toxicity, (2) radiation therapy will reduce local recurrence better than after surgery (3) 20% are incurable surgically at presentation. Conclusions: Primary surgical treatment of anal cancer may remain safe and cost-effective in low resource settings